Intravenous Thrombolysis After Reversal of Dabigatran With Idarucizumab in Acute Ischemic Stroke: A Case Report - Xie, Dan; Wang, Xuefan; Li, Yao; Chen, Ruiling; Zhao, Yingying; Xu, Chunling; Zhang, Qian; Zhang, Yongbo (Frontiers in Aging Neuroscience, 2021)
Background: As there is a growing concern about the cerebral embolism events secondary to non-valvular atrial fibrillation, novel oral anticoagulant (NOAC) has been more and more widely used as an anticoagulation treatment for prevention of stroke. However, in the face of life-threatening bleeding or emergency surgery/treatment, NOAC-related antagonists such as idarucizumab need to be urgently used to reverse the NOAC. Using recombinant tissue plasminogen activator（rt-PA）intravenous thrombolysis for acute ischemic stroke requires a time window of 4.5 hours. This case reports rt-PA intravenous thrombolysis after reversal of dabigatran anticoagulation with idarucizumab in patients with acute ischemic stroke. Case presentation: We report the case of 62-year-old Chinese female with non-valvular atrial fibrillation treated with dabigatran 110mg twice daily, and missed a dose on the eve of the stroke. The patient presented with acute ischemic stroke causing the angle of mouth deviated to right side and left limb weakness in the early morning of the next day. Due to the last dosing time of dabigatran was between 24-48 hours, the patients were given rt-PA intravenous thrombolysis after reversal of dabigatran anticoagulation with idarucizumab, while any potential relativeall contraindications had been excluded by means of laboratory test and CT scan in the hospitalization services. NIHSS score was reduced from 4 to 1, and the patient was discharged after 2 weeks. Conclusion: Our case report adds to the evidence that idarucizumab administration is safe and effective in the setting of patients with atrial fibrillation treated with dabigatran who develop acute ischemic stroke requiring rt-PA intravenous thrombolysis.